(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
This study discusses the practice of the bombon system which is a tradition of the Kadazandusun community. The bombon system is a method of conservation of freshwater fish that has been practiced by the Kadazandusun since the time of their ancestors. Through this practice, the Kadazandusun community can preserve their environment, while at the same time ensuring a continuous source of fish. The bombon tradition is based on the traditional beliefs and customary laws of the Kadazandusun people. The bombon system shows the local wisdom of the Kadazandusun community towards the environment and in human relations. The problem around which this study is centred relates to the structural functionalism of the bombon system in the life of the Kadazandusun community. The objective of this study is to look at the function and role of the practice of the bombon system in the life of the Kadazandusun community. This study was conducted via field study, employing interviews, participatory observations and document research. The results show that the bombon system and the Kadazandusun community are functional and support each other’s survival. The practice of the bombon system becomes a functional aesthetic requirement for the community of bombon practitioners, furthering its role as a contributor to the values and culture of the practitioner community. The practice of the bombon system, which highlights many implicit and explicit positive effects in the life of the Kadazandusun community, proves that the practice is functional and continues to be relevant to the life of the community today. Keywords: Traditional beliefs, customary laws, local wisdom, bombon, Kadazandusun